2020
DOI: 10.1155/2020/9092829
|View full text |Cite
|
Sign up to set email alerts
|

AQUACOAST: A Simulation Tool to Explore Coastal Groundwater and Irrigation Farming Interactions

Abstract: In the framework of coastal groundwater-dependent irrigation agriculture, modelling becomes indispensable to know how this renewable resource responds to complex (usually not conceptualized nor monitored) biophysical, social, and economic interactions. Friendly user interfaces are essential to involve nonmodeling experts in exploiting and improving models. Decision support systems (DSS) are software systems that integrate models, databases, or other decision aids and package them in a way that decision makers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…(i) GDM1 (rangelands): water erosion in rangelands and shrublands [28,37,44,45] for Dehesas in Cáceres province (DL3) and Sierra de Los Filabres in Almería province (DL5) (ii) GDM2 (croplands): water erosion in extensive croplands for olive orchards (DL1) and wheat/ sunflower crops rotation (DL2) in Córdoba province [46] (iii) GDM3 (irrigation agriculture): hydrological models linked to groundwater-based irrigation agriculture [36,47,48] for Eastern La Mancha aquifer in Ciudad Real and Albacete provinces apply to DL4…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) GDM1 (rangelands): water erosion in rangelands and shrublands [28,37,44,45] for Dehesas in Cáceres province (DL3) and Sierra de Los Filabres in Almería province (DL5) (ii) GDM2 (croplands): water erosion in extensive croplands for olive orchards (DL1) and wheat/ sunflower crops rotation (DL2) in Córdoba province [46] (iii) GDM3 (irrigation agriculture): hydrological models linked to groundwater-based irrigation agriculture [36,47,48] for Eastern La Mancha aquifer in Ciudad Real and Albacete provinces apply to DL4…”
Section: Resultsmentioning
confidence: 99%
“…e former relies on the current stock of natural resources, the physical framework (climate and soil type), and a limiting factor, the dynamics of which can be affected by the stock of resources. In fact, soil erosion, soil salinization, saltwater intrusion, and others have an inhibitory effect on resource regeneration that can be irreversible once critical thresholds are exceeded [36].…”
Section: A Generic Desertificationmentioning
confidence: 99%
“…The higher central aspect of C1 indicates that the articles published within the scope of agriculture, article, and classification are concerned more with crop classification. Some of the recent publications within C1 focus on digital soil mapping (Lagacherie et al, 2022), an intelligence-based approach for agricultural soil prediction (Nguyen et al, 2022), AI-based apple leaf disease classification (Al-Wesabi et al, 2022), and simulating various water-deficit regimes for irrigation scheduling optimization (Martínez-Valderrama et al, 2020). Recent publications indicate that C1 is more inclined toward procedures and classification of multiple aspects of agriculture segments.…”
Section: Thematic Mapmentioning
confidence: 99%
“…rough this application, the authors found that the new algorithm might provide valuable reference information for groundwater quality monitoring management. e paper "AQUACOAST: A Simulation Tool to Explore Coastal Groundwater and Irrigation Farming Interactions" [2] introduces a tool to analyse the impact of apparently unrelated factors such as the prices of crops, subsidies, or exploitation costs on the advance of saltwater intrusion, a great threat to coastal groundwater-dependent irrigation agriculture systems. e tool implements a system dynamics model in Vensim software that considers the integration of hydrological, agronomic, and economic drivers, and a Venapp push-button interface that allow users access to a Vensim model without going through the Vensim modelling environment.…”
Section: Published Papersmentioning
confidence: 99%